Interaction Effects of Vitamin D Receptor Polymorphisms and Vitamin D3 Supplementation on Plasma Oxidative Stress and Apoptotic Biomarkers Among Breast Cancer Survivors (P05-027-19). (13th June 2019) - Kazemin, Elham; Jamshidi-naeini, Yasaman; Akbari, Mohammad Esmaeil; Moradi, Nariman; Gharibzadeh, Safoora; Amouzegar, Atieh; Mondul, Alison; Khademolmele, Maryam; Ghodoosi, Nasim; Zarins, Katie R; Davoodi, Sayed Hossein; Rozek, Laura
Abstract: Objectives: Interactions of human genes and environmental exposures play a crucial role in cancer etiology and prognosis. We investigated whether response to vitamin D3 supplementation in terms of plasma oxidative stress (OS) and apoptotic biomarkers were mediated by the vitamin D receptor ( VDR ) single-nucleotide polymorphisms (SNPs) among breast cancer survivors. Methods: Two hundred and fourteen women who were diagnosed with breast cancer (invasive or in situ) and had completed all treatment regimens received 4000 IU of vitamin D3 daily for 12 weeks. Anthropometric, dietary, sun exposure, physical activity, as well as laboratory assessments including plasma superoxide dismutase (SOD), total antioxidant capacity (TAC), malondialdehyde (MDA), 8-hydroxy-2′-deoxyguanosine (8-OHdG), and Bcl2 were performed at enrolment and post-intervention. VDR genotyping was performed at ApaI, TaqI, FokI, BsmI, and Cdx-2. Linear regression was used to analyze whether the effect of vitamin D3 supplementation on response variables was modulated by the selected VDR SNPs. Results: Linear regression analysis adjusted for age, BMI, on-study plasma 25(OH)D changes, and baseline circulating 25(OH)D indicated that the AA genotype of the ApaI on VDR was associated with greater increase and decrease in plasma Bcl2 [0.21, 95% Confidence Interval (CI) (0.03, 0.39)] and MDA [−0.68, 95% CI (−1.35, −0.02)] compared to aa respectively. This association did not remain statistically significant after correction for multiple testing. Overall, we found no statistically significant interaction of the VDR SNPs and inferred haplotypes with the circulating OS and apoptotic biomarkers except for the FokI BsmI ApaI haplotype and circulating MDA (p-value for global score = 0.02) after multiple testing correction. Conclusions: Our findings indicate a weak interaction between the VDR haplotypes and responses of plasma OS and apoptotic biomarkers to vitamin D3 supplementation. However, further assessments of additional genes and biomarkers with longer intervention periods may further explain the complex interplay between genes and nutrients. Funding Sources: Cancer Research Center, National Nutrition and Food Technology Research Institute, and the Endocrine Research Center of Shahid Beheshti University of Medical Sciences.